Structure and content of tourists' physical training at the stage of preliminary basic training - V.G. Savchenko; N.V. Moskalenko; O.S. Mikitchik; O.R. Gorbonos-Andronova; O.V. Lukina (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
The purpose of the research is to substantiate scientifically the structure and content of tourists' physical training at the stage of preliminary basic training. Material and methods . The study involved athletes aged 12-13 years. The control and experimental groups consist of 32 young men in each group. Results . It was developed and experimentally substantiated the structure and content of athletes-tourists' physical training. It was determined the content and volumes of physical training types (general, special and additional). It was developed the complexes of training exercises with a rational correlation of general and additional physical training means. The ratio of the main types of training was as follows: general physical training - 35%, special - 15% and additional - 50%. Conclusions . The rock climbing and slacklining were offered for the preparatory period as the means of additional physical training. These means are based on the structure of motor activity and preferential orientation focused on the development of coordination, power, speed and speed-power qualities.